Study on application of horizontal and vertical sub surface flow constructed wetland for landfill leachate treatment - Mohd Abd Hafiz Zakaria (Penerbit Universiti Malaysia Perlis, 2011)
Leachate is one of the major problems in landfill since it contained high levels of organic and inorganic matters. As it was highly contaminated, leachate could not be discharged directly into the surface water bodies. Constructed wetlands are highly efficient and low-cost alternative treatment systems for treating leachate. The main purpose of this study was to compare the efficiency of horizontal subsurface flow system (HSSF) and vertical subsurface flow system (VSSF) in the treatment of COD, nutrients (NH3-N and PO4-P) and heavy metals (Fe and Mn) present in landfill leachate by the use of constructed wetland systems. The amount of nutrient and heavy metals uptake by the plant (Limnocharis flava), and the amount of heavy metals retained in the soil media was also investigated. A laboratory-scale study was conducted on subsurface flow constructed wetland systems operated in vertical and horizontal mode. Each system comprises of one planted system and one control system.